دور الممارسات القيادية الداعمة في تنمية الكفاءة المهنية دراسة ميدانية بالمؤسسة العمومية للصحة الجوارية بوسعادة - طيبي فتيحة; رحموني صورية; اشراف: بسطي نور الدين (جامعة محمد بوضياف -المسيلة, 2025)
هدفت دراستنا الى التعرف على دور الممارسات القيادية في تنمية الكفاءة المهنية وذلك من خلال محاولة الوصول الى الاهداف التالية: - معرفة دور التمكين الوظيفي في تنمية الكفاءة الفنية. - معرفة دور التعليم في الرفع من مستوى الكفاءة الفكرية. - معرفة دور عدالة المعاملات في الرفع من مستوى الكفاءة الانسانية. وللوصول الى تحقيق هذه الأهداف تم اتباع المنهج الوصفي التحليلي، وتضمنت جانبا نظريا واخر ميدانيا وقد تم استخدام استمارة الاستبيان والملاحظة لجمع المعلومات من مجتمع الدراسة، حيث تم توزيع الاستبيان على عينة قدرها 30 مفردة وتمت معالجة البيانات باستخدام البرنامج الاحصائي SPPS. الكلمات المفتاحية: الممارسات القيادية الداعمة، تنمية الكفاءة المهنية Abstract: Our study aimed to identify the role of leadership practices in developing professional competence by trying to reach the following goals: Knowing the role of job empowerment in developing technical competence. Knowing the role of education in raising the level of intellectual competence. Knowing the role of fair transactions in raising the level of human efficiency. To achieve these goals، the descriptive analytical approach was followed because it is consistent with the topics of the social sciences، and it included a theoretical aspect and a field aspect. The questionnaire and observation were used to collect information from the study population. The questionnaire was distributed to a sample of 30 individuals and the data was processed. Using the SPPS statistical program. Keywords: supportive leadership practices. Developing professional competence